Peel waste of citrus fruits: A valuable and renewable source of polyphenols for the treatment of diabesity - Muhammad Ajmal Shah; Savaira Tariq; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Ifat Alsharif; Khairul Anam; Reem T. Almutairi; Khalid A. Al-Regaiey; Ahmad O. Babalghith; Uzma Saleem; Abd. Malik; et al. (Current Research in Biotechnology, 2024)
Diabesity is the concurrence of both diabetes and obesity, and it has become a modern epidemic. It is linked by numerous common pathophysiological mechanisms which can be targeted to combat its harms. The available treatments for diabesity include the medications that are also causing several adverse side effects. The increasing healthcare costs, both direct and indirect, for diabesity management continue to rise, underscoring the urgency to find efficient and cost-effective treatment methods. These circumstances have prompted a shift in research towards exploring natural dietary alternatives for treatment. Among these dietary substitutes, citrus fruits rich in polyphenols have caught the attention of researchers. This review narrates the major interconnection of diabesity and brings out the various mechanisms in which citrus polyphenols can be used for its management. Citrus polyphenols fight against diabesity by targeting adipokines, reactive oxygen species, leptin deficiency, metabolic endotoxemia, peroxisomes proliferator activating receptors, insulin signaling, starch hydrolyzing enzymes, and human islet amyloid polypeptide. The studies on the role of citrus polyphenols in the treatment of diabesity have shown clearly that addressing various physiological systems which can interact with citrus polyphenols can help to manage diabesity and related health concerns.